On fecundity of chum salmon Oncorhynchus keta in the commercial herd at Iturup Island - A. N. Elnikov; O. V. Zelennikov (Известия ТИНРО)
Absolute fecundity of chum salmon Oncorhynchus keta is investigated for the commercial herd dwelled at Iturup Island. Currently, the herd is formed mostly by fish of hatchery origin but has retained the same species and regional features that distinguished it when it was formed mainly due to natural spawning. The value of absolute fecundity is determined for 3833 females and ranges from 769 to 4400 oocytes. For the fish of two dominant age groups (3+ and 4+), this number usually decreases with age, with the exception of particularly large older fish with greater fecundity. Same factors that promote abundance of hatchery fish in the herd also contribute to decreasing of abortive processes in the ovaries, therefore the absolute fecundity correlates closely and positively with the catch of chum salmon in the coastal waters.